INTERRELATIONSHIP BETWEEN FIXED AND SITUATIONAL MENTAL ENTITIES - Nadareishvili , Vakhtang (Georgian Psychological Journal, 2022)
According to our assumption, D. Uznadze’s situational set is a mental entity, similarly to attitude, person- ality trait and ﬁxed set. Situational set is the basis of the formation of ﬁxed set and vice versa (i.e. it can be a further diﬀerentiation ﬆage of ﬁxed set, its product). Fixed dispositions are realized in behavior through situational set. For this purpose, situational set orga- nizes the ﬆructural components of the ﬁxed disposition and unites them with the actual givenness of a speciﬁc moment. In addition, successful behavioral realization ensured by situational set improves the characteriﬆics of dispositional set (ნადირაშვილი, 1985) and increases the eﬀectiveness of adaptation achieved through its participation.At the high levels of mental activity, behavior is regulated with the involvement of conscious resources. The article focuses on conscious regulation, which, for the purpose of analysis, is diﬆinguished from the unconscious regulation ensured by underlying set. The above resources take part in the internalization of social values and their use for the formation of individual/personal sets.The proposed approach conﬁrms a) an organic relationship between diﬀerent forms and types of set; b) the possibility of their synergic relationship and mutual transformation; c) the exiﬆence of diﬀerent, but mutually supplementary sources (including the sources of socio-cultural origin, e.g. common values) en- dowing activity with the needed energy; d) the possibility and necessity of the inclusion of D. Uznadze’s situational set in the international theoretical and methodological context related to ‘dispositional’ con- ﬆructs.Our approach is also productive for the further elaboration of the relationship between the conﬆituents of legal culture (e.g. legal awareness) and normative behavior when their unity is based on two, interrelated forms of set – ﬁxed and non-ﬁxed disposition, i.e. ‘dispositional’ and situational sets.